OS6.2 Identifying molecular subtypes of non-enhancing glioma using MRI perfusion and diffusion parameters. (19th September 2018) - Koene, S; Incekara, F; van der Voort, S; Vincent, A; van den Bent, M; Lycklama à Nijeholt, G; Nandoe Tewari, R; Smits, M
Abstract: Background: According to the 2016 WHO classification low grade glioma can be classified into three groups based on molecular profile. A non-invasive method to identify these molecular profiles has yet to be established. There is evidence MRI perfusion and diffusion imaging might aid in the differentiation of the molecular profiles. Our aim is to identify MR imaging parameters to distinguish molecular profiles of non-enhancing glioma. Material and Methods: 96 patients with non-enhancing, presumed low grade glioma were included. Patients were included if a pre-operative MRI-scan was available including at least T2w/FLAIR, dynamic susceptibility contrast perfusion and diffusion imaging and if the molecular status - 1p/19q co-deletion status and IDH mutation - was known. Tumors were segmented semi-automatically. Imaging parameters such as relative Cerebral Blood Volume (rCBV) and Apparent Diffusion Coefficient (ADC) were derived using IB Neuro. Tumors were divided into three clinically relevant molecular subgroups; 1p/19q co-deletion with IDH mutation (n=39), IDH-mutation without co-deletion (n=37), and IDH-wildtype without co-deletion (n=20). Results: Kruskall-Wallace test showed significant differences for rCBV (Median, 75 th and 85 th percentile) and ADC (Median, 15 th and 25 th percentile) values between the three groups (p<0.05). Post-hoc analysis showed that IDH-mutated tumors without co-deletion had a significantly lower rCBV compared to the 1p/19q-codeleted tumors and the IDH-wildtype tumors (Median rCBV 0.67, 0.98 and 1.02 respectively p<0.05). Also, IDH-mutated, non-codeleted tumors have a significantly higher ADC compared to the two other groups (Median ADC 1.52 versus 1.27 and 1.17 p<0.05). No significant differences were found between 1p/19q co-deleted tumors and IDH-wildtype tumors in ADC or rCBV. Multinomial regression analysis (with age, tumor location and median rCBV/ADC ratio) showed an accurate prediction of the molecular profile of 79.2%. Conclusion: IDH-mutated, non-codeleted tumors had a significantly lower rCBV and significantly higher ADC compared to IDH-wildtype and 1p/19q co-deleted tumors. These results suggest that MRI perfusion and diffusion parameters are promising to determine mutation status of non-contrast enhancing low grade glioma.